Análise de um queimador infravermelho funcionando com combustível híbrido : GLP/Bio-óleo - Azevedo Neto, Aluísio (2010)
Biomass is considered the largest renewable energy source that can be used in an environmentally sustainable. From the pyrolysis of biomass is possible to obtain products with higher energy density and better use properties. The liquid resultant of this process is traditionally called bio-oil. The use of infrared burners in industrial applications has many advantages in terms of technical-operational, for example, uniformity in the heat supply in the form of radiation and convection, with a greater control of emissions due to the passage of exhaust gases through a macroporous ceramic bed. This paper presents a commercial infrared burner adapted with an ejector proposed able to burn a hybrid configuration of liquefied petroleum gas (LPG) and bio-oil diluted. The dilution of bio-oil with absolute ethanol aimed to decrease the viscosity of the fluid, and improving the stability and atomization. It was introduced a temperature controller with thermocouple modulating two stages (low heat / high heat), and solenoid valves for fuels supply. The infrared burner has been tested, being the diluted bio-oil atomized, and evaluated its performance by conducting energy balance. The method of thermodynamic analysis to estimate the load was used an aluminum plate located at the exit of combustion gases and the distribution of temperatures measured by thermocouples. The dilution reduced the viscosity of the bio-oil in 75.4% and increased by 11% the lower heating value (LHV) of the same, providing a stable combustion to the burner through the atomizing with compressed air and burns combined with LPG. Injecting the hybrid fuel there was increase in the heat transfer from the plate to the environment in 21.6% and gain useful benefit of 26.7%, due to the improved in the efficiency of the 1st Law of Thermodynamics of infrared burner